Binominal quantifiers in Spanish: syntagmatic and paradigmatic analogy in interaction. (January 2016) - Verveckken, Katrien
Abstract: Within the framework of grammaticalization, analogy is usually considered as a precondition for change. One of the hotly debated topics is its status as a mechanism or a motivation for change. The present paper aims to investigate the role of analogy in the development of Spanish binominal quantifiers and zooms in on the histories of seven quantifying nouns, viz., aluvión, barbaridad, (h)atajo, letanía, mar, montón and pila . The distinct nature of the developmental pathways followed tones down the triggering force or coercing impact of rather schematic constructions. Analogy is operationalized as a two-dimensional process: a clear distinction is made between paradigmatic analogical thinking (which motivates change) and syntagmatic analogical thinking (which also constrains change and interacts with conceptual persistence). In addition, analogical mechanisms are at work both construction-internally and construction-externally. Highlights: Binominal quantifiers (BQs) are considered as a locus of grammaticalization. Three uses are distinguished: head, quantifier and (two-way) specifier. Analogy is approached as a two-dimensional mechanism. Analogy and conceptual persistence interact in the development/synchronic use of BQs.